Large Scale Internet-based Survey of Patients With a Myeloproliferative Neoplasm: Opinions and Experiences Regarding SARS-CoV-2 (COVID-19) Vaccination Strategies in 2021. Issue 7 (23rd July 2021) - Saunders, Jamie; Curto-Garcia, Natalia; Sriskandarajah, Priya; O'Sullivan, Jennifer; Woodley, Claire; Asirvatham, Susan; Campbell-Drew, Marion; Mathias, Jonathan; Ellis, Tim; Baker, Nona; Radia, Deepti H.; Ali, Sahra; et al.
Abstract : Supplemental Digital Content is available in the text.